Hydrogen exchange properties of proteins in native and denatured states monitored by mass spectrometry and NMR. - Chung, E; Nettleton, E; Morgan, C; Gross, M; Miranker, A; Radford, SE; Dobson, C; Robinson, C (1997)
The extent of deuterium labeling of hen lysozyme, its three-disulfide derivative, and the homologous alpha-lactalbumins, has been measured by both mass spectrometry and NMR. Different conformational states of the proteins were produced by varying the solution conditions. Alternate protein conformers were found to contain different numbers of 2H atoms. Furthermore, measurement in the gas phase of the mass spectrometer or directly in solution by NMR gave consistent results. The unique ability of mass spectrometry to distinguish distributions of 2H atoms in protein molecules is exemplified using samples prepared to contain different populations of 2H-labeled protein. A comparison of the peak widths of bovine alpha-lactalbumin in alternate solution conformations but containing the same average number of 2H atoms showed dramatic differences due to different 2H distributions in the two protein conformers. Measurement of 2H distributions by ESI-MS enabled characterization of conformational averaging and structural heterogeneity. In addition, a time course for hydrogen exchange was examined and the variation in distributions of 2H atom compared with simulations for different hydrogen exchange models. The results clearly show that exchange from the native state of bovine alpha-lactalbumin at 15 degrees C is dominated by local unfolding events.